Connotation analysis and path discussion of China’s land-sea coordination policy: based on the interregional externality theory - Yanping Li; Yuping Wang; Dahai Liu; Yuting Hou (Frontiers in Marine Science, 2024)
As two spatial geographic units that are both independent of each other and closely linked, the land and sea have complex spatial interactions. Therefore, China implements the land-sea coordination policy (LSC) needs to be approached from a more macroscopic, systematic and comprehensive perspective. Based on the interregional externality theory, this study takes the land-sea coordination policy of China as an example, and focuses on the interaction process and manifestation between land and sea, and then explores the connotation and realization path of LSC. Firstly, we delineated the spatial unit and analyzed the land-sea interactions (LSI) using Vensim software. Secondly, the characteristics and manifestations of LSI are summarized from the perspective of interregional externalities. Finally, this study elucidates the foundational concept of implementing LSC and further propose actionable pathways for promoting land and sea development in a coordinated way, aimed at offering supportive decision-making insights for achieving LSC within the broader framework of China’s territorial spatial planning. Initiating LSC implementation involves strategies such as source control, process management, and interaction interface optimization. Deepening LSC effectiveness entails strengthening positive interregional externalities while mitigating negative interregional externalities.